Cognitive intrusion of pain and catastrophic thinking independently explain interference of pain in the activities of daily living. (August 2017) - Talaei-Khoei, Mojtaba; Ogink, Paul T.; Jha, Ragini; Ring, David; Chen, Neal; Vranceanu, Ana-Maria
Abstract: Patients with musculoskeletal illness often report that pain interferes with their ability to engage in activities of daily living. Catastrophic thinking is consistently depicted as an important cognitive factor that hinders adjustment to pain. Current research has also shown that pain negatively impacts an individual's ability to maintain attention on the task at hand. While a measure of the experience of cognitive intrusion of pain (ECIP) has been recently developed to quantify the extent of that impact, little research has explored this issue in everyday settings. This study tested the mediating roles of cognitive intrusion of pain and pain catastrophizing scale (PCS) on the association of pain intensity with pain interference in 142 patients with upper-extremity musculoskeletal illness. We found that both cognitive intrusion of pain ( b = 0.136, bootstrap SE = 0.048, 95% BCa CI [0.052, 0.245]) and pain catastrophizing ( b = 0.114, bootstrap SE = 0.044, 95% BCa CI [0.047, 0.221]) partly and independently mediated the relationship between pain intensity and pain interference. Although comparable, the mediation effect of cognitive intrusion of pain was slightly larger than that of pain catastrophizing (25.7%, bootstrap SE = 0.094 vs. 21.5%, bootstrap SE = 0.080). Results suggest that pain sensations can interfere with activities of daily living through two distinct mechanisms. A combination of traditional cognitive behavioral therapy and mindfulness skills training targeting both pain catastrophizing and cognitive intrusion has the potential to decrease pain interference and help patients return to normal healthy living in spite of acute or persistent pain.